Slovak Republic : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2001)
During 1996-98, the measured fiscal deficits have substantially underestimated the extent of the fiscal problem in Slovakia. Amid these signs of vulnerability, the present government has assumed office in October 1998, and embarked on policies to restore macroeconomic balances and lay the basis for sustainable economic growth. The fiscal tightening and developments in the nongovernment sector has led to a sharp fall in domestic demand in 1999, but a strong improvement in net trade performance partly offset their impact on aggregate demand.